Degradation of Proton Exchange Membrane (PEM) Water Electrolysis Cells: Looking Beyond the Cell Voltage Increase. Issue 10 (25th June 2019) - Suermann, Michel; Bensmann, Boris; Hanke-Rauschenbach, Richard
Abstract : The degradation of proton exchange membrane water electrolysis cells is usually measured in a temporal increase of the cell voltage. Although this is sufficient to evaluate the stability of a system, it is less suitable for targeted material development. Thus, an overpotential-specific and temporally resolved electrochemical characterization protocol is proposed. In this the ohmic overpotential is determined with high frequency resistance measurements. These are also used in combination with polarization curves to distinguish between the kinetic and mass transport overpotentials and to determine kinetic key parameters, according to the Butler-Volmer and transition state theory. Complementary electrochemical impedance spectroscopy measurements further unravel the individual resistances. On this basis, the following statements can already be issued. The major share of the measured cell voltage increase, i.e. degradation, is of apparent nature as it is recovered once lower potentials are applied. It is suggested that this is due to changes in the oxidation states of the iridium-based catalyst. Real degradation occurs in the ohmic and mass transport overpotential mainly at higher current densities and longer operating times. The increasing kinetic overpotential with increasing operating time is primarily potential-driven. Interestingly, both the Tafel slope and the apparent exchange current density slightly increase over time.